Lithium ion secondary battery
By regulating the composition of the electrolyte and the average particle size of the silicon-based material, the problem of volume expansion and low conductivity of the silicon-based negative electrode in the lithium-ion secondary battery is solved, and the high and low temperature performance of the battery is improved.
Patent Information
- Application Number
- CN202411982840.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In lithium-ion secondary batteries, the silicon-based negative electrode has significant volume expansion and low conductivity during charging and discharging, resulting in poor performance of high and low temperatures.
By designing the composition of the electrolyte, the sum of the contents of methyl trifluoropropionate and the first additive, as well as the content ratio of fluorovinyl carbonate and 1,3-propane sulfonate lactone in the first additive, the density and stability of the SEI film are enhanced; at the same time, the average particle size of the silicon-based material is adjusted to make it have a higher dispersion and specific surface area.
It improves the high-temperature floating charging performance and low-temperature discharge performance of the battery, alleviates the cyclic expansion of the silicon-based negative electrode, improves the infiltration and contact of the electrolyte, and enhances the ion transmission efficiency.
Smart Images

Figure BDA0005221913070000201
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to lithium-ion secondary batteries. Background Art
[0002] With the rapid development of new energy vehicles, portable electronic devices and other markets, the requirements for battery performance are increasing. Silicon-based materials have become an ideal substitute for traditional carbon-based materials (such as graphite) due to their ultra-high theoretical specific capacity (4200mAh / g), and are regarded as the first choice for the negative electrode materials of the next generation of lithium-ion batteries; however, silicon-based negative electrodes face the problems of significant volume expansion (volume expansion rate can reach 300%) and low conductivity during the charging and discharging process, resulting in poor high and low temperature performance. Therefore, how to improve the conductivity of silicon-based negative electrode lithium-ion secondary batteries and alleviate volume expansion is crucial to improving the high and low temperature performance of lithium-ion secondary batteries. Summary of the invention
[0003] The purpose of the present invention is to solve the battery performance degradation caused by cyclic expansion and low conductivity of a lithium ion secondary battery (hereinafter referred to as battery) including a silicon-based negative electrode, especially to improve the high temperature and low temperature performance of the battery. A lithium ion secondary battery is proposed. By designing the composition of an electrolyte, the sum of the contents of methyl trifluoropropionate and a first additive in the electrolyte and the content ratio of fluoroethylene carbonate and 1,3-propane sultone in the first additive are regulated to enhance the compactness and stability of a SEI film and construct a stable SEI film. On the other hand, by adjusting the average particle size of a silicon-based material so that it has high dispersibility and specific surface area, it is helpful to increase the contact area between the silicon-based material and the electrolyte, maintain structural stability during volume expansion, and improve the high temperature and low temperature performance of the battery.
[0004] In order to solve the above problems, the inventors of the present invention propose the following technical solutions:
[0005] A lithium-ion secondary battery comprises an electrolyte and a negative electrode sheet, wherein the electrolyte comprises methyl trifluoropropionate and a first additive, wherein based on the total weight of the electrolyte, the content of the methyl trifluoropropionate is A, the content of the first additive is B, and 10%≤A+B≤35%; the first additive comprises fluoroethylene carbonate and 1,3-propane sultone; based on the total weight of the electrolyte, the content ratio of fluoroethylene carbonate to 1,3-propane sultone is 1-20; the negative electrode sheet comprises a negative electrode active material, wherein the negative electrode active material comprises a silicon-based material, and the average particle size of the silicon-based material is D, and D is 6μm-20μm.
[0006] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0007] (1) In the present invention, by adjusting the average particle size of the silicon-based material within a suitable range, the cyclic expansion of the silicon-based negative electrode can be alleviated on the one hand, and the infiltration and contact of the electrolyte can be improved on the other hand, thereby improving the ion transmission efficiency.
[0008] (2) In the present invention, methyl trifluoropropionate and the first additive are added to the electrolyte, which can improve the density and generation efficiency of the SEI film, improve the antioxidant property of the electrolyte, and reduce the occurrence of side reactions; and the content relationship between fluoroethylene carbonate and 1,3-propane sultone in the first additive is regulated, thereby alleviating the effect of the addition of fluoroethylene carbonate on high-temperature performance, so that the battery has good high and low-temperature performance at the same time.
[0009] (3) The lithium-ion secondary battery provided by the present invention has good high-temperature floating charge performance and low-temperature discharge performance.
[0010] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. DETAILED DESCRIPTION
[0011] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0012] A lithium ion secondary battery comprises an electrolyte and a negative electrode sheet, wherein the electrolyte comprises methyl trifluoropropionate and a first additive, wherein based on the total weight of the electrolyte, the content of the methyl trifluoropropionate is A, the content of the first additive is B, 10%≤A+B≤35%, for example, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 33%, 34% or 35%.
[0013] In one embodiment, 14%≤A+B≤24%.
[0014] In the present invention, the first additive includes fluoroethylene carbonate (FEC) and 1,3-propane sultone (PS).
[0015] In the present invention, the electrolyte includes methyl trifluoropropionate and a first additive. Among them, the first additive includes FEC and PS. FEC can effectively construct a LiF-rich and structurally stable SEI film, can effectively alleviate the volume expansion of silicon-based materials, and maintain the stable cycle of the negative electrode sheet. However, FEC has poor structural stability in a high temperature environment. When FEC is added in excess, the dissociation rate of the fluorine element therein is accelerated to generate HF, which reacts with carbonates in the SEI film and CEI film to generate CO2, destroy the interface film, and aggravate the decomposition of the electrolyte at the interface; in addition, HF will also aggravate the decomposition of LiPF6 and solvents, resulting in gas production and high-temperature performance degradation. PS has good chemical stability at high temperatures and can remain relatively stable under high temperature and high voltage conditions. The use of FEC and PS in combination can enhance the stability and compactness of the SEI film, effectively alleviate the poor structural stability of FEC in a high temperature environment, resulting in battery gas production and high-temperature performance deterioration. When the temperature rises, it can effectively slow down the dissociation rate of FEC, reduce the occurrence of side reactions, and improve gas production. Therefore, the use of the first additive is beneficial to improving the volume expansion of the silicon-based material and making the high temperature performance of the battery relatively stable.
[0016] However, adding excessive FEC and PS to the electrolyte will affect the viscosity and ion migration speed of the electrolyte at low temperatures. Methyl trifluoropropionate has a low freezing point characteristic, which can improve the fluidity of the electrolyte in a low temperature environment, which is beneficial to the improvement of the lithium ion migration speed, thereby improving the performance of the battery at low temperatures. And methyl trifluoropropionate can also form an SEI film at the negative terminal. Therefore, the first additive can complement methyl trifluoropropionate, improve the density and stability of the SEI film, and significantly improve the high-temperature floating charge performance and low-temperature discharge performance of the battery. However, it is not enough to add only methyl trifluoropropionate and the first additive to the electrolyte, and the content of the two needs to be limited. When the sum of the contents of the two, A+B, is less than 10%, the content of methyl trifluoropropionate and / or the first additive in the electrolyte is too little, the SEI film formed at the negative terminal is insufficient and the structure is incomplete, which is not conducive to alleviating the side reactions of battery charging and discharging, and is insufficient to improve the high and low temperature performance of the battery; when A+B>35%, methyl trifluoropropionate and / or the first additive in the electrolyte are added excessively, resulting in aggravated battery bulging, increased interface film thickness, increased impedance, and thus loss of active lithium and deterioration of cycle performance.
[0017] The above technical solutions can improve the high and low temperature performance of the battery and the volume expansion during the charge and discharge cycle to a certain extent, but the improvement effect is limited. The inventors of the present invention further found that by further adjusting the content ratio of FEC and PS and the average particle size of the silicon-based material, the volume expansion of the battery can be effectively alleviated and the battery can have excellent high and low temperature performance. The reason is:
[0018] First, as mentioned above, FEC has poor structural stability in high temperature environments, while PS has good chemical stability at high temperatures. If the content relationship between the two is not limited, the improvement of the high temperature performance of the battery will be limited. When the content ratio of FEC to PS is less than 1, the content of FEC relative to PS is too low. At this time, the structural stability of the SEI film formed at the negative electrode is poor, which will cause the SEI film to rupture and form repeatedly, consume a large amount of lithium ions, aggravate the side reactions between the negative electrode material and the electrolyte, and is not conducive to improving the cycle stability of the battery. When the content ratio of FEC to PS is greater than 20, the content of PS relative to FEC is too low, and PS is not enough to alleviate the gas production of FEC in a high temperature environment, making the high temperature performance of the battery worse.
[0019] Second, by adjusting the average particle size of the silicon-based material, it can cooperate with the aforementioned electrolyte, thereby alleviating the volume expansion of the silicon-based material during the lithiation process and increasing the lithium ion transmission rate. If the average particle size of the silicon-based material is too large, the lithium ion transmission rate will be reduced, which is not conducive to the low-temperature performance of the battery; and if the average particle size of the silicon-based material is too small, the contact area with the electrolyte will increase, which is not conducive to the formation and stability of the SEI (solid electrolyte interface) film, thereby affecting the high and low temperature performance of the battery.
[0020] In summary, by synergistically controlling the average particle size of the silicon-based material and the composition of the electrolyte, the battery can have lower volume expansion and can take into account both high and low temperature performance.
[0021] In the present invention, based on the total weight of the electrolyte, the content ratio of fluoroethylene carbonate to 1,3-propane sultone is 1-20, for example, 1, 2, 3, 4, 5, 6, 8, 10, 12, 14, 16, 17, 18, 19 or 20.
[0022] In the present invention, the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a silicon-based material. The average particle size of the silicon-based material is D, and D is 6μm-20μm, for example, 6μm, 6.2μm, 6.4μm, 6.6μm, 6.8μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.
[0023] In one embodiment, D is 8 μm-15 μm.
[0024] In the present invention, the average particle size of the silicon-based material can be obtained by conventional testing methods in the art, such as by combining a scanning electron microscope with image analysis software, specifically as follows: first obtain a high-resolution image through a scanning electron microscope, and then perform particle size measurement and distribution statistics through electron microscope image analysis software such as ImageJ to obtain the average particle size, and the model of the scanning electron microscope is Sigma300 / 500.
[0025] In the present invention, 5%≤B≤30%, for example, 5%, 5.2%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 29.2%, 29.4%, 29.6%, 29.8% or 30%.
[0026] In the present invention, 0%<A≤10%, for example, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.2%, 9.4%, 9.6%, 9.8% or 10%.
[0027] In one embodiment, 1≤A≤5%.
[0028] In the present invention, 5%≤B≤30%, for example, 5%, 5.2%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 29.2%, 29.4%, 29.6%, 29.8% or 30%.
[0029] In one embodiment, 12%≤B≤23%.
[0030] In the present invention, based on the total weight of the electrolyte, the content of FEC is 5%-20%, for example, 5%, 5.2%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0031] In the present invention, based on the total weight of the electrolyte, the content of PS is 1%-5%, for example, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.
[0032] In the present invention, the contents of methyl trifluoropropionate, FEC and PS in the electrolyte can be obtained by conventional testing methods in the art, such as by gas chromatography or gas chromatography-mass spectrometry.
[0033] In the present invention, 0.85≤(A+B) / D≤3.75, for example, 0.85, 0.9, 0.95, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6 or 3.75.
[0034] In one embodiment, 1.3≤(A+B) / D≤2.9.
[0035] In the present invention, when the electrolyte is combined with a silicon-based negative electrode, there is a problem of cyclic expansion of the silicon-based negative electrode. The relationship between the sum of the contents of methyl trifluoropropionate and the first additive in the electrolyte and the average particle size of the silicon-based material in the negative electrode sheet is further regulated, so that the electrolyte composition can be matched with the silicon-based negative electrode. By limiting (A+B) / D to meet the above range, efficient synergy can be generated between the fluoroethylene carbonate, the first additive and the silicon-based material in the electrolyte. On the one hand, a uniform and complete interface film is generated on the surface of the silicon-based negative electrode to protect the silicon-based negative electrode from aggravated side reactions, thereby alleviating the expansion of the negative electrode; on the other hand, the matching of the electrolyte and the silicon-based material can be improved. By optimizing the composition of the electrolyte, the adverse effects of the particle size effect of the silicon-based material can be alleviated to a certain extent, so that the cyclic expansion of the negative electrode is alleviated, and the high-temperature floating charge and low-temperature discharge performance of the battery are improved.
[0036] In some embodiments, the first additive further comprises ethylene sulfate (DTD). Based on the total weight of the electrolyte, the content of the DTD is 0%-2%, for example, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%.
[0037] In the present invention, DTD can optimize the interface, reduce impedance, make the electrolyte have good oxidation resistance, reduce the side reaction of the electrolyte, and improve high and low temperature performance.
[0038] In the present invention, the content of DTD in the electrolyte can be obtained by conventional testing methods in the art, such as by gas chromatography or gas chromatography-mass spectrometry.
[0039] In the present invention, the electrolyte may further include a second additive, wherein the second additive includes vinylene carbonate (VC) and / or vinyl ethylene carbonate (VEC).
[0040] In the present invention, based on the total weight of the electrolyte, the content of VC is 0%-2%, for example, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%.
[0041] In the present invention, based on the total weight of the electrolyte, the content of VEC is 0%-2%, for example, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%.
[0042] In the present invention, vinylene carbonate and vinyl ethylene carbonate in the electrolyte can be obtained by conventional testing methods in the art, such as by gas chromatography or gas chromatography-mass spectrometry.
[0043] In the present invention, the electrolyte includes a carbonate solvent, and the carbonate solvent includes ethylene carbonate and / or at least one of the following fluorine-substituted or unsubstituted solvents: propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0044] In the present invention, based on the total weight of the electrolyte, the content of the carbonate solvent is C, 30%≤C≤60%, for example, 30%, 31%, 32%, 33%, 35%, 37%, 39%, 42%, 45%, 48%, 50%, 52%, 55%, 56%, 57%, 58%, 59% or 60%.
[0045] In the present invention, the carbonate solvent has a high oxidation potential, which can effectively improve the antioxidant properties of the electrolyte, thereby reducing the side reactions of the electrolyte. When the carbonate solvent with high antioxidant properties is used in combination with methyl trifluoropropionate in the electrolyte, the side reactions of the electrolyte in high-temperature floating charge and overcharge tests can be effectively reduced, and the oxidative decomposition of the electrolyte by transition metal ions can be reduced, thereby further improving the high temperature performance and overcharge safety performance of the battery.
[0046] In the present invention, the content of the carbonate solvent in the electrolyte can be obtained by conventional testing methods in the art, such as by gas chromatography or gas chromatography-mass spectrometry.
[0047] In the present invention, the median particle size Dv50 of the silicon-based material is 6μm-20μm, for example, 6μm, 6.2μm, 6.4μm, 6.6μm, 6.8μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.
[0048] In the present invention, the silicon-based material is regulated to have a uniform particle size distribution, which helps to form a stable and thin SEI film and maintain the stability of the battery during the cycle; if the particle size distribution is uneven, it may cause the storage capacity in some areas to be too high and other areas to be low, thereby affecting the overall performance of the battery.
[0049] In the present invention, the negative electrode active material further comprises a carbon-based material, and the particle size Dv'10 of the carbon-based material is 4 μm-11 μm, for example, 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, 5 μm, 5.2 μm, 5.4 μm, 5.6 μm, 5.8 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm or 11 μm; the median particle size Dv'5 0 is 8μm-25μm, for example, 8μm, 8.2μm, 8.4μm, 8.6μm, 8.8μm, 9μm, 9.2μm, 9.4μm, 9.6μm, 9.8μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm or 25μm.
[0050] In the present invention, regulating the particle size and particle size distribution of carbon-based materials helps to improve the stability and reactivity of negative electrode active materials, as well as the cycle and rate performance of batteries. When the particle size of the carbon-based material is too large, the adhesion between the carbon-based material and the negative electrode current collector is not strong enough, and loose structures and pores are easily generated, resulting in reduced strength and insufficient compactness of the carbon-based material; in addition, the conductive paths between carbon-based materials with large particle sizes are not smooth, resulting in reduced conductivity, which in turn causes the performance of negative electrode active materials to decline, affecting battery performance, such as rate performance; and when the particle size of the carbon-based material is too small, it is easier to react with electrolytes and other media, affecting the stability and service life of the negative electrode active material; at the same time, carbon-based materials with small particle sizes are more likely to produce microcracks and pulverization during the charge and discharge process, resulting in the shedding of negative electrode active materials and capacity attenuation.
[0051] In the present invention, the median particle size Dv50 of the silicon-based material, the particle size Dv'10 and the median particle size Dv'50 of the carbon-based material can be obtained by conventional testing methods in the art, such as using a laser particle size analyzer and measuring by laser diffraction, the equipment model is Mastersize 3000.
[0052] In the present invention, the lithium-ion secondary battery includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes at least one of the Ni element, the Co element, and the Mn element.
[0053] In the present invention, the positive electrode active material includes a chemical formula of Li a Ni b Co x Mn y A z O2 substances, 0.9≤a<1.1 (for example, 0.9, 0.92, 0.94, 0.96, 0.98, 0.1, 0.15, 0.2, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.02, 1.05, 1.07 or 1.09), 0≤b<1 (for example, 0, 0.02, 0.04, 0.06, 0.08, 0.1, 0.15, 0.2, 0.3, 0.4, 0.52, 0.6, 0.7, 0.8, 0.9, 0.92, 0.94, 0.96, 0.98 or 0.99), 0<x≤1 (for example, 0.02, 0.04, 0.06, 0. 0.02, 0.04, 0.06, 0.08, 0.1, 0.15, 0.2, 0.3, 0.4, 0.52, 0.6, 0.7, 0.8, 0.9, 0.92, 0.94, 0.96, 0.98, 0.99 or 1), 0≤y<1 (for example, 0, 0.02, 0.04, 0.06, 0.08, 0.1, 0.15, 0.2, 0.3, 0.4, 0.52, 0.6, 0.7, 0.8, 0.9, 0.92, 0.94, 0.96, 0.98 or 0.99), 0<z≤0.05 (for example, 0.01, 0.02, 0.03, 0.04 or 0.05), A includes at least one of Al, Mg, Ti, Zr, Y, La and W.
[0054] In the present invention, based on the total weight of Ni element, Co element, Mn element and A, the content of Ni element is 50%-100%, for example, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 75%, 80%, 85%, 90%, 92%, 94%, 96%, 98% or 100%.
[0055] In the present invention, the positive electrode active material is combined with the electrolyte containing the first additive to form a CEI film at the positive terminal and effectively reduce the dissolution of transition metal ions at the positive terminal. Since the electrolyte also has high antioxidant properties, the occurrence of electrolyte side reactions is alleviated and gas expansion is suppressed, thereby improving the high-temperature cycle and high-temperature storage performance of the battery.
[0056] In the present invention, the chemical composition of the positive electrode active material can be measured by conventional methods in the art, for example, by the following method: taking about 0.1 g of a sample, adding 10 mL of hydrochloric acid, and digesting it on a 350° C. hot plate for 10 min, cooling and fixing the volume to 100 ml, and then diluting it 10 times, taking part of the solution for analysis with an ICP spectrometer, and obtaining the corresponding test parameters, and calculating the chemical composition of the positive electrode active material.
[0057] In the present invention, the silicon-based material includes silicon-carbon material.
[0058] In the present invention, the specific surface area of the silicon-carbon material is 0.5 m 2 / g-10m 2 / g, for example 0.5m 2 / g, 0.6m 2 / g, 0.8m 2 / g, 1m 2 / g, 1.2m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2m 2 / g, 2.4m 2 / g, 2.8m 2 / g, 3.2m 2 / g, 3.6m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g or 10m 2 / g.
[0059] In the present invention, regulating the specific surface area of the silicon-carbon material can regulate the contact between the negative electrode active material and the electrolyte and the reaction activity of the negative electrode active material. A larger specific surface area is beneficial to increasing the contact area between the negative electrode active material and the electrolyte, forming more active sites to participate in the reaction, thereby improving the electrochemical activity of the battery. However, too large a specific surface area will lead to the formation of more SEI films, thereby consuming more electrolyte and active lithium, and reducing the initial coulombic efficiency.
[0060] In the present invention, the specific surface area of the silicon-carbon material can be measured by conventional testing methods in the art, such as the Brunauer-Emmett-Teller (BET) test method, such as using a Tri StarⅡ specific surface analyzer for measurement, with N2 as the adsorbed gas.
[0061] In the present invention, the average sphericity of the silicon-carbon material is 0.5-1, for example, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.96, 0.98 or 1.
[0062] In the present invention, regulating the average sphericity of silicon-carbon materials is beneficial to improving the cycle stability and rate performance of the battery; silicon-carbon materials with high average sphericity can more fully utilize the negative electrode active material during the charge and discharge process, thereby improving the cycle stability and rate performance of the battery; at the same time, they have better wettability in the electrolyte and can more effectively contact and react with the electrolyte; in addition, silicon-carbon materials with high average sphericity can also evenly disperse the mechanical stress during the volume expansion of the particles, making the particles less likely to break, thereby improving the cycle retention rate of the battery.
[0063] In the present invention, the average sphericity can be analyzed by image processing software (such as Image Pro Plus) on the image of each particle in the SEM photograph of the negative electrode active material at a certain magnification (such as 2500 times), and the circumference and area of each particle are obtained, and the circumference equivalent radius r1 and the area equivalent radius r2 of each particle are calculated respectively. Then, the average sphericity of each particle S=r2 / r1, and then the average sphericity of each particle is quantitatively weighted averaged to obtain the average sphericity of the silicon-carbon material.
[0064] In the present invention, the oil absorption value of the silicon-carbon material is 10mL / 100g-100mL / 100g, for example, 10mL / 100g, 12mL / 100g, 30mL / 100g, 14mL / 100g, 16mL / 100g, 18mL / 100g, 20mL / 100g, 40mL / 100g, 50mL / 100g, 60mL / 100g, 70mL / 100g, 80mL / 100g, 90mL / 100g or 100mL / 100g.
[0065] In the present invention, the oil absorption value of the silicon-carbon material is related to the liquid retention amount of the battery. As the oil absorption value increases, the liquid retention amount of the battery increases. During the battery cycling process, with the consumption of the electrolyte and the occurrence of side reactions, when the electrolyte decreases, lithium ions lose the channels for migration between the positive and negative active materials, which will cause problems such as lithium plating, volume expansion, and gas generation in the battery, thus affecting the high and low temperature performance of the battery. Controlling the oil absorption value within a certain range can make the formed SEI film more complete and uniform, and improve the structural stability of the silicon-carbon particles in the negative active material.
[0066] In the present invention, the oil absorption value of the silicon-carbon material can be measured by conventional testing methods in the art, for example, in the following manner: scrape off the negative active material layer of the negative electrode plate, wash off the binder, and dry it (in a vacuum drying oven at 100 °C for 12 h) to obtain the negative active material powder. Weigh the mass m1 of a clean beaker and glass rod, add 5 g of the negative active material powder and record the total mass m2. Gradually add dioctyl phthalate (DOP) drop by drop with a burette and stir well. Stop adding (DOP) when a lump is formed. Weigh the total weight m3 of the beaker at this time. Then the oil absorption value = (m3 - m2) / (m2 - m1) × 100, and the oil absorption value of the silicon-carbon particles is obtained by weighted average.
[0067] In the present invention, the carbon-based material includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.
[0068] In the present invention, the silicon-based material may further include at least one of nanosilicon (Si) and silicon oxide material (SiO x (0 < x < 2)).
[0069] In the present invention, the electrolyte further includes a carboxylic acid ester solvent, and the carboxylic acid ester solvent includes at least one of fluorine-substituted or unsubstituted propyl acetate, n-butyl acetate, isobutyl acetate, n-pentyl acetate, isopentyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate, and n-ethyl butyrate.
[0070] In the present invention, the electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (FSI), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methyl, and lithium bis(trifluoromethylsulfonyl)imide.
[0071] In the present invention, the electrolyte includes a third additive, and the third additive includes at least one of vinyl sulfate, lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, succinonitrile (SN), glutaronitrile, adiponitrile (AND), pimelonitrile, suberonitrile, sunflower dinitrile, 1,3,6-hexanetrinitrile, glycerol trinitrile, 1,2-bis(2-cyanoethoxy)ethane and propenyl-1,3-sultone.
[0072] In the present invention, the positive electrode sheet also includes a positive electrode current collector, a positive electrode conductor and a positive electrode binder, and all of them are conventional choices of those skilled in the art. For example, the positive electrode current collector includes aluminum foil, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), polyacrylate, polyimide and styrene-butadiene rubber, and the positive electrode conductor includes at least one of acetylene black, conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene.
[0073] In the present invention, the negative electrode sheet also includes a negative electrode current collector, a negative electrode conductor and a negative electrode binder, and all of them are conventional choices of those skilled in the art. For example, the negative electrode current collector includes copper foil, the negative electrode binder includes at least one of polyacrylic acid (PAA), sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, polyimide, styrene-butadiene rubber (SBR) and polyvinylidene fluoride, and the negative electrode conductor includes at least one of acetylene black, conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene.
[0074] In the present invention, the lithium-ion secondary battery further comprises a separator, which is conventionally selected in the art, such as a polyethylene separator.
[0075] In the present invention, the lithium-ion secondary battery also includes a positive electrode sheet, which includes a positive electrode collector, a positive electrode conductor and a positive electrode binder, and all of which are conventional choices of those skilled in the art. For example, the positive electrode collector includes aluminum foil, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), polyacrylate, polyimide and styrene-butadiene rubber, and the positive electrode conductor includes at least one of acetylene black, conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene.
[0076] In the present invention, the negative electrode sheet also includes a negative electrode current collector, a negative electrode conductor and a negative electrode binder, and all of them are conventional choices of those skilled in the art. For example, the negative electrode current collector includes copper foil, the negative electrode binder includes at least one of polyacrylic acid (PAA), sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, polyimide, styrene-butadiene rubber (SBR) and polyvinylidene fluoride, and the negative electrode conductor includes at least one of acetylene black, conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene.
[0077] In the present invention, the upper limit voltage of the lithium-ion secondary battery is 4.2V or above. The term upper limit voltage has the conventional meaning in the art, and generally refers to the maximum voltage value that the battery can safely reach during charging. Continuing to charge beyond the upper limit voltage may cause the battery to be overcharged, thereby shortening the battery life and even causing safety risks.
[0078] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.
[0079] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0080] In the following examples, unless otherwise specified, all materials used were commercially available of analytical grade.
[0081] The following examples are used to illustrate the lithium ion secondary battery of the present invention.
[0082] Embodiment 1:
[0083] Preparation of electrolyte: In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), a carbonate solvent (content X, X=40%) and propyl propionate (PP) are mixed to form an organic solvent, wherein the carbonate solvent is a mixture of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) in a ratio of 3:3:14; based on the total weight of the electrolyte, methyl trifluoropropionate (content A, A=3%) and a first additive (content B, B=19%) are added to the organic solvent, and stirred evenly to form a mixed solvent, wherein the first additive is FEC (content FEC, PC) and diethyl carbonate (DEC). c1, c1=15%), PS (content is c2, c2=3%), DTD (content is recorded as c3, c3=1%); then based on the total weight of the electrolyte, 3% of the third additive and 22% of the lithium salt are added to the obtained electrolyte, wherein the third additive is composed of lithium difluorophosphate: lithium difluorooxalate borate = 1:2, and the lithium salt is composed of 15% lithium hexafluorophosphate (LiPF6) and 7% lithium bis(trifluoromethanesulfonyl imide) (FSI), stirring evenly, and after passing the moisture and free acid tests, an electrolyte is obtained, wherein the weight content of the organic solvent, methyl trifluoropropionate, the first additive, the lithium salt and the third additive sums up to 100%.
[0084] Among them, A+B=22%, and the content ratio of FEC and PS c1 / c2=5.
[0085] Preparation of positive electrode:
[0086] The positive electrode active material (811NCM), conductive carbon black and polyvinylidene fluoride are evenly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the front and back sides of an aluminum foil; and the positive electrode sheet is obtained by drying and rolling.
[0087] Preparation of negative electrode:
[0088] Artificial graphite (median particle size Dv'50 is 11.3 μm), silicon carbon material (average particle size D is 10.5 μm, median particle size Dv50 is 10.5 μm), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are evenly mixed in a mass ratio of 78.5:20.5:0.5:0.25:0.25, deionized water is added, and the mixture is fully stirred to form a uniform negative electrode slurry; the negative electrode slurry is coated on a copper foil, dried, rolled, cut and cleaned to obtain a negative electrode sheet.
[0089] At this time, (A+B) / D is 2.095.
[0090] Assembly of lithium-ion secondary batteries:
[0091] The prepared positive electrode sheet, negative electrode sheet and diaphragm (polyethylene film) are placed in order so that the diaphragm is between the positive electrode sheet and the negative electrode sheet, and then the pole ears are welded and wound to obtain a core, which is then placed in an aluminum-plastic film packaging bag, followed by liquid injection, formation, secondary sealing and sorting processes to prepare a lithium-ion secondary battery, and finally the electrical performance of the battery is tested.
[0092] Embodiment 2:
[0093] Preparation of electrolyte: In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), a carbonate solvent (content X, X=42%) and propyl propionate (PP) are mixed to form an organic solvent, wherein the carbonate solvent is ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) mixed in a ratio of 3:3:14; based on the total weight of the electrolyte, methyl trifluoropropionate (content A, A=2%) and a first additive (content B, B=12%) are added to the organic solvent, stirred evenly, to form a mixed solvent, wherein the first additive is FEC (content c1, c1=10%), PS (content c2, c2=1%), DTD (content recorded as c3, c3=1%); then based on the total weight of the electrolyte, adding 3% of the third additive and 22% of the lithium salt to the obtained electrolyte, wherein the third additive consists of lithium difluorophosphate: lithium difluorooxalate borate = 1:2, and the lithium salt consists of 15% of lithium hexafluorophosphate (LiPF6) and 7% of lithium bis(trifluoromethanesulfonyl imide) (FSI), stirring evenly, and after passing the moisture and free acid tests, obtaining an electrolyte, wherein the weight content of the organic solvent, methyl trifluoropropionate, the first additive, the lithium salt and the third additive sums up to 100%.
[0094] Among them, A+B=14%, and the content ratio of FEC and PS c1 / c2=10.
[0095] Preparation of positive electrode:
[0096] The positive electrode active material (811NCM), conductive carbon black and polyvinylidene fluoride are evenly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the front and back sides of an aluminum foil; and the positive electrode sheet is obtained by drying and rolling.
[0097] Preparation of negative electrode:
[0098] Artificial graphite (median particle size Dv'50 is 12.6 μm), silicon carbon material (average particle size D is 8 μm, median particle size Dv50 is 8 μm), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are evenly mixed in a mass ratio of 78.5:20.5:0.5:0.25:0.25, deionized water is added, and the mixture is fully stirred to form a uniform negative electrode slurry; the negative electrode slurry is coated on a copper foil, dried, rolled, cut and cleaned to obtain a negative electrode sheet.
[0099] At this time, (A+B) / D is 1.75.
[0100] Assembly of lithium-ion secondary batteries:
[0101] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene film) are placed in order so that the separator is between the positive electrode sheet and the negative electrode sheet, and then the pole ears are welded and wound to obtain a core, which is then placed in an aluminum-plastic film packaging bag, followed by liquid injection, formation, secondary sealing and sorting processes to prepare a lithium-ion secondary battery, and finally the electrical performance of the battery is tested.
[0102] Embodiment 3:
[0103] Preparation of electrolyte: In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), a carbonate solvent (content X, X=50%) and propyl propionate (PP) are mixed to form an organic solvent, wherein the carbonate solvent is a mixture of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) in a ratio of 3:3:14; based on the total weight of the electrolyte, methyl trifluoropropionate (content A, A=1%) and a first additive (content B, B=23%) are added to the organic solvent, and stirred evenly to form a mixed solvent, wherein the first The additives are composed of FEC (content is recorded as c1, c1=18%), PS (content is recorded as c2, c2=4%), and DTD (content is recorded as c3, c3=1%); based on the total weight of the electrolyte, 3% of the third additive and 15% of the lithium salt are added to the obtained electrolyte, wherein the third additive is composed of lithium difluorophosphate: lithium difluorooxalate borate = 1:2, and the lithium salt is lithium hexafluorophosphate (LiPF6), and the electrolyte is obtained after being stirred evenly and passed the moisture and free acid tests, wherein the weight content of the organic solvent, methyl trifluoropropionate, the first additive, the lithium salt and the third additive sums up to 100%.
[0104] Among them, A+B=24%, and the content ratio of FEC and PS c1 / c2=4.5.
[0105] Preparation of positive electrode:
[0106] The positive electrode active material (811NCM), conductive carbon black and polyvinylidene fluoride are evenly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the front and back sides of an aluminum foil; and the positive electrode sheet is obtained by drying and rolling.
[0107] Preparation of negative electrode:
[0108] Artificial graphite (median particle size Dv'50 is 9.2 μm), silicon carbon material (average particle size D is 8.3 μm, median particle size Dv50 is 8.3 μm), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are evenly mixed in a mass ratio of 78.5:20.5:0.5:0.25:0.25, deionized water is added, and the mixture is fully stirred to form a uniform negative electrode slurry; the negative electrode slurry is coated on a copper foil, dried, rolled, cut and cleaned to obtain a negative electrode sheet.
[0109] At this time, (A+B) / D is 2.892.
[0110] Assembly of lithium-ion secondary batteries:
[0111] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene film) are placed in order so that the separator is between the positive electrode sheet and the negative electrode sheet, and then the pole ears are welded and wound to obtain a core, which is then placed in an aluminum-plastic film packaging bag, followed by liquid injection, formation, secondary sealing and sorting processes to prepare a lithium-ion secondary battery, and finally the electrical performance of the battery is tested.
[0112] Embodiment 4:
[0113] Preparation of electrolyte: In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), a carbonate solvent (content X, X=53%) and propyl propionate (PP) are mixed to form an organic solvent, wherein the carbonate solvent is a mixture of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) in a ratio of 3:3:14; based on the total weight of the electrolyte, methyl trifluoropropionate (content A, A=5%) and a first additive (content B, B=14.5%) are added to the organic solvent, stirred evenly to form a mixed solvent, wherein the first additive An additive is composed of FEC (content is recorded as c1, c1=12%), PS (content is recorded as c2, c2=2%), and DTD (content is recorded as c3, c3=0.5%); based on the total weight of the electrolyte, 3% of a third additive and 15% of a lithium salt are added to the obtained electrolyte, wherein the third additive is composed of lithium difluorophosphate: lithium difluorooxalate borate=1:1, and the lithium salt is lithium hexafluorophosphate (LiPF6); stirring is uniform, and after passing the moisture and free acid tests, an electrolyte is obtained, wherein the weight content of the organic solvent, methyl trifluoropropionate, the first additive, the lithium salt and the third additive sums up to 100%.
[0114] Among them, A+B=19.5%, and the content ratio of FEC and PS c1 / c2=6.
[0115] Preparation of positive electrode:
[0116] The positive electrode active material (811NCM), conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on the front and back sides of the aluminum foil; and the positive electrode sheet is obtained by drying and rolling.
[0117] Preparation of negative electrode:
[0118] Artificial graphite (median particle size Dv'50 is 10.5 μm), silicon carbon material (average particle size D is 15 μm, median particle size Dv50 is 15 μm), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are evenly mixed in a mass ratio of 78.5:20.5:0.5:0.25:0.25, deionized water is added, and the mixture is fully stirred to form a uniform negative electrode slurry; the negative electrode slurry is coated on a copper foil, dried, rolled, cut and cleaned to obtain a negative electrode sheet.
[0119] At this time, (A+B) / D is 1.3.
[0120] Assembly of lithium-ion secondary batteries:
[0121] The prepared positive electrode sheet, negative electrode sheet and diaphragm (polyethylene film) are placed in order so that the diaphragm is between the positive electrode sheet and the negative electrode sheet, and then the pole ears are welded and wound to obtain a core, which is then placed in an aluminum-plastic film packaging bag, followed by liquid injection, formation, secondary sealing and sorting processes to prepare a lithium-ion secondary battery, and finally the electrical performance of the battery is tested.
[0122] Embodiment 5 group:
[0123] This group of examples is used to verify the impact of the change of "D", which is achieved by adjusting the average particle size of the silicon-carbon material, as follows:
[0124] Example 5a is based on Example 1, except that D=6 μm, the median particle size Dv50 of this silicon-based material is 6 μm, and (A+B) / D is 3.667.
[0125] Example 5b is based on Example 1, except that D=20 μm, the median particle size Dv50 of the silicon-based material is 20 μm, and (A+B) / D is 1.1.
[0126] Embodiment 6 group:
[0127] This group of examples is used to verify the influence of the change of "A+B", which is achieved by changing the content of methyl trifluoropropionate and the first additive in the electrolyte, as follows:
[0128] Example 6a is based on Example 3, except that A=5%, B=23%. In this case, A+B=28%, and (A+B) / D is 3.373.
[0129] Example 6b is based on Example 2, except that A=1%, B=12%. In this case, A+B=13%, and (A+B) / D is 1.625.
[0130] Embodiment 7:
[0131] This embodiment is used to verify the impact of the change in "c1 / c2". It is based on Embodiment 1, and the difference is that c1=18%, c2=1%. At this time, c1 / c2=18, B=20%, A+B=23%, and (A+B) / D is 2.19.
[0132] Embodiment 8 group:
[0133] This group of examples is used to verify the impact of the change of "(A+B) / D", as follows:
[0134] Example 8a is based on Example 3, except that D=8 μm, A=5%. In this case, A+B=28%, and (A+B) / D is 3.5.
[0135] Example 8b is based on Example 2, except that D=15 μm, A=1%, in which case A+B=13%, and (A+B) / D is 0.867.
[0136] Embodiment 9 group:
[0137] This group of examples is used to verify the impact of changes in the "content X of the polycarbonate solvent", as follows:
[0138] Example 9a is based on Example 1, except that the content X of the polycarbonate solvent is 30% based on the total weight of the electrolyte.
[0139] Example 9b is based on Example 1, except that the content X of the polycarbonate solvent is 60% and the lithium salt is 15% lithium hexafluorophosphate (LiPF6) based on the total weight of the electrolyte.
[0140] Example 10 Group:
[0141] This group of examples is used to verify the impact of the change in the "median particle size Dv'50 of the carbon-based material", as follows:
[0142] Example 10a is based on Example 1, except that the median particle size Dv'50 of the carbon-based material is 8 μm.
[0143] Example 10b is based on Example 1, except that the median particle size Dv'50 of the carbon-based material is 25 μm.
[0144] Embodiment 11:
[0145] This embodiment is used to verify the influence of the change of "A". It is based on Embodiment 1, but the difference is that A=10%. In this case, A+B=29%, and (A+B) / D is 2.762.
[0146] Embodiment 12 group:
[0147] This group of examples is used to verify the impact of the change of the "second additive", as follows:
[0148] Example 12a is based on Example 1, except that the second additive consists of FEC (content denoted as c1, c1=14.5%), PS (content denoted as c2, c2=3%), DTD (content denoted as c3, c3=1%), and the second additive consists of VC (vinyl carbonate, content denoted as c4, c4=0.5%).
[0149] Example 12b is based on Example 1, except that the first additive consists of FEC (content denoted as c1, c1=14.5%), PS (content denoted as c2, c2=3%), and DTD (content denoted as c3, c3=1%), and the second additive consists of VEC (vinyl ethylene carbonate, content denoted as c5, c5=0.5%).
[0150] In the above embodiments, the particle size Dv'10 of the carbon-based material is in the range of 4 μm-11 μm, and the specific surface area of the silicon-carbon material is in the range of 0.5 m 2 / g-10m 2 / g range, the average sphericity of the silicon-carbon materials is in the range of 0.5-1, and the oil absorption value of the silicon-carbon materials is in the range of 10mL / 100g-100mL / 100g.
[0151] Comparative Example 1:
[0152] This group of comparison ratios is used to verify the impact of the change in "D", as follows:
[0153] Comparative Example 1a is based on Example 1, except that D=24.5 μm, the median particle size Dv50 of the silicon-based material is 24.5 μm, and (A+B) / D is 0.898.
[0154] Comparative Example 1b is based on Example 1, except that D=2.8 μm, the median particle size Dv50 of the silicon-based material is 2.8 μm, and (A+B) / D is 7.857.
[0155] Comparative Example 2 Group:
[0156] This group of comparison ratios is used to verify the impact of the change of "A+B", as follows:
[0157] Comparative Example 2a is based on Example 1, except that, based on the total weight of the electrolyte, A=1%, B=8%, wherein c1=6.5%, c2=1%, c3=0.5%, and A+B=9%, (A+B) / D is 0.45.
[0158] Comparative Example 2b is based on Example 1, except that, based on the total weight of the electrolyte, A=10%, B=27%, the lithium salt is 15% lithium hexafluorophosphate (LiPF6), wherein c1=20%, c2=5%, c3=2%, at this time A+B=37%, (A+B) / D is 6.167.
[0159] Comparative Example 3 Group:
[0160] This group of comparison ratios is used to verify the impact of the change in "c1 / c2", as follows:
[0161] Comparative Example 3a is based on Example 1, except that c1=25%, c2=1%, at which time c1 / c2=25, B=27%, A+B=30%, and (A+B) / D is 2.857.
[0162] Comparative Example 3b is based on Example 1, except that c1=5%, c2=6.5%, at which time c1 / c2=0.77, B=12.5%, A+B=15.5%, and (A+B) / D is 1.476.
[0163] Comparative Example 4:
[0164] Based on Example 1, the difference is that no methyl trifluoropropionate is added to the electrolyte, that is, A=0%, at this time A+B=19%, and (A+B) / D is 1.81.
[0165] Test example:
[0166] (1) 45℃ floating charge test:
[0167] The battery obtained from the embodiment of the present invention and the comparative example is placed in a constant temperature environment of 25°C, and its charge is adjusted to 50% SOC. The initial thickness T1 of the battery is tested when the material is received. The battery is placed in a constant temperature environment of 45°C, and is charged at a constant current and constant voltage of 0.5C to an upper limit voltage of 4.3V. The constant voltage charging is performed for 7 days as a cycle, and the thermal thickness expansion change of the battery is monitored. The final hot thickness T2 of the battery after 45°C float charge is tested with obvious inflation of the battery as the limiting condition. The thickness expansion rate of the lithium battery at 45°C float charge = (T2-T1) / T1×100%.
[0168] (2) -30℃ low temperature discharge test:
[0169] The batteries obtained from the embodiments of the present invention and the comparative examples were placed in a constant temperature environment at 25°C, the batteries were discharged at 0.2C to 3.0V, and charged at 0.7C constant current and constant voltage to an upper limit voltage of 4.3V, with a cut-off current of 0.05C. After the batteries were fully charged, they were left for 5 minutes, and then discharged at 0.5C constant current to a cut-off voltage of 3.0V, and the discharge capacity of the batteries at 25°C and 0.5C was recorded as the initial capacity Q1; in a constant temperature environment at 25°C, the batteries were charged at 0.7C constant current and constant voltage to 4.45V, with a cut-off current of 0.05C to fully charge the batteries, and then the fully charged batteries were placed in a -30°C environment and left to stand for 4H. When the surface temperature of the batteries reached the ambient temperature, they were discharged at 0.5C to 3.0V, and the discharge capacity of the batteries at -30°C and 0.5C was recorded as Q2, and the -30°C low-temperature discharge capacity retention rate of the batteries was calculated as Q2 / Q1×100%.
[0170] (3) 0.25C-10V overcharge test:
[0171] Under the condition of ambient temperature (25±5)℃, charge the discharged battery at a constant current of 0.25C until it reaches 10V, then change to constant voltage charging, and stop charging when the charging time limit is 6H.
[0172] Judgment criteria: The battery has passed if it does not catch fire or explode.
[0173] The performance tests of the batteries obtained in the examples of the present invention and the comparative examples are recorded in Table 1.
[0174]
[0175] It can be seen from Table 1 that the lithium ion secondary battery prepared by the present invention has good high-temperature floating charge, low-temperature discharge and overcharge safety compared with the comparative example.
[0176] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium ion secondary battery, characterized in that: The lithium ion secondary battery comprises an electrolyte and a negative electrode sheet, wherein the electrolyte comprises methyl trifluoropropionate and a first additive, and based on the total weight of the electrolyte, the content of the methyl trifluoropropionate is A, the content of the first additive is B, and 10%≤A+B≤35%; The first additive includes fluoroethylene carbonate and 1,3-propane sultone; based on the total weight of the electrolyte, the content ratio of fluoroethylene carbonate to 1,3-propane sultone is 1-20; The negative electrode sheet includes a negative electrode active material, the negative electrode active material includes a silicon-based material, and the average particle size of the silicon-based material is D, and D is 6 μm-20 μm.
2. The lithium ion secondary battery according to claim 1, wherein The first additive also includes ethylene sulfate, and the content of ethylene sulfate is 0%-2%; and / or, 14% ≤ A + B ≤ 24%; and / or, the content ratio of fluoroethylene carbonate to 1,3-propane sultone is 4.5-10; And / or, D is 8μm-15μm.
3. The lithium ion secondary battery according to claim 1 or 2, wherein: 0%<A≤10%; and / or, 5% ≤ B ≤ 30%; And / or, 0.85≤(A+B) / D≤3.
75.
4. The lithium ion secondary battery according to claim 3, wherein: 1%≤A≤5%; and / or, 12% ≤ B ≤ 23%; And / or, 1.3≤(A+B) / D≤2.
9.
5. The lithium ion secondary battery according to claim 1, wherein Based on the total weight of the electrolyte, the content of the fluoroethylene carbonate is 5%-20%; And / or, the content of 1,3-propane sultone is 1%-5%.
6. The lithium ion secondary battery according to claim 1, wherein The electrolyte includes a second additive, wherein the second additive includes vinylene carbonate and / or vinyl ethylene carbonate; and / or, the electrolyte comprises a carbonate solvent, the carbonate solvent comprising ethylene carbonate and / or at least one of the following fluorine-substituted or unsubstituted solvents: propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate; Preferably, based on the total weight of the electrolyte, the content of the carbonate solvent is C, 30%≤C≤60%.
7. The lithium ion secondary battery according to claim 1, wherein The negative electrode active material further comprises a carbon-based material, wherein the particle size Dv'10 of the carbon-based material is 4 μm-11 μm, and the median particle size Dv'50 is 8 μm-25 μm.
8. The lithium ion secondary battery according to claim 1, wherein The lithium-ion secondary battery includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes at least one of a Ni element, a Co element, and a Mn element.
9. The lithium ion secondary battery according to claim 8, wherein: The positive electrode active material includes a general formula of Li a Ni b Co x Mn y A z O2 compound, 0.9≤a<1.1, 0≤b<1, 0<x≤1, 0≤y<1, 0<z≤0.05, wherein A comprises at least one of Al, Mg, Ti, Zr, Y, La and W; Preferably, based on the total weight of the Ni element, the Co element, the Mn element and the A, the content of the Ni element is 50%-100%.
10. The lithium ion secondary battery according to claim 1, wherein The silicon-based material includes a silicon-carbon material; Preferably, the specific surface area of the silicon-carbon material is 0.5 m 2 / g-10m 2 / g; Preferably, the average sphericity of the silicon-carbon material is 0.5-1; Preferably, the oil absorption value of the silicon-carbon material is 10 mL / 100 g-100 mL / 100 g.
Citation Information
Patent Citations
Lithium ion secondary battery
CN114976205A
Electrolyte, electrochemical device and electronic device
CN116544503A
Secondary battery containing silicon-based negative electrode
CN117080361A
Electrolyte containing lithium carbonate and lithium ion battery containing electrolyte
CN118943493A
Lithium-ion battery electrolyte and lithium-ion battery
WO2024114166A1
Cited By
Battery cell, battery device and electric device
CN120545473A